Nitrogen metabolism and protein requirements for maintenance of growing Red Norte bulls - Amorim, T. R.; Silva, A. L.; Ladeira, M. M.; Chizzotti, M. L.; Cunha, C. S.; Machado Neto, O. R. [UNESP]; Carvalho, J. R. R.; Corte, R. R. P. S.; Mueller, L. F.; Pereira, A. S. C.; Marcondes, M. (Cambridge Univ Press, 2020)
Dietary protein adjustments can reduce environmental impact and economic losses in production systems. However, we lack information regarding nitrogen (N) metabolism and protein requirements for maintenance of crossbred animals such as Red Norte breed, precluding a precise dietary management. The objective was to evaluate the effect of increasing dietary CP levels (9%, 11%, 13%, 15% and 17%) on intake, digestibility and N balance, as well as to estimate the metabolizable protein requirements for maintenance (MPm) of growing Red Norte bulls. Thirty five animals averaging 280 +/- 4.0 kg BW were fed during 45 days in a 60 : 40 forage : concentrate ratio diet in which the last 5 days were used for the digestibility trial. Intakes of CP and non-fibrous carbohydrates (NFCs) and feed efficiency linearly increased (P < 0.05) as CP levels increased, while DM, NDF, nitrogen efficiency use and ether extract were not influenced by CP levels (P > 0.05). Digestibilities of DM, organic matter, ether extract, NFC and CP as well as metabolizable energy intake linearly increased (P < 0.05), and true digestibility of CP was not affected (P > 0.05) by treatments. Urinary N and retained N linearly increased (P < 0.05) with the increase in dietary N. The MPm were estimated as 4.46 g/BW0.75 and the efficiency of use of MPm was 0.673. In conclusion, obtained MPm requirements of growing Red Norte bulls are greater than the values reported in literature for Zebu cattle and dietary CP levels of 15% and 17% exhibited great responses for growing Red Norte cattle. However, a cost-benefit evaluation should be done before its use.
Keywords: bovine; crossbreed; metabolizable protein; nitrogen balance; retained nitrogen